Risk Factor Associated with Hepatitis B Incidence in Pondok Pesantren Putri Ibnul Qoyyim Yogyakarta - Aini, Resmi; Susiloningsih, Jarwati (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2013)
Hepatitis B virus has been a problem in developing countries. The transmission of HBV is through the exposure to the blood or secret of the infected patients. Woman has 3 times higher risk to get HBV than men. The pleminary observation revealed that in Pondok Pesantren Putri QoyyimYogyakarta 20-30 students shared a room. It also showed poor hygene that might lead to environmental based transmission. No sepesific sympthom for HBV infection in the early phase causes people unaware of getting infected. This study was aimed at finding out factors associated with HBV case among students in Pondok Pesantren Putri Ibnul Qoyyim Yogyakarta. This was an observational study using Cross Sectionl approach including 97 female students. The data were collected using interview, observation and blood testing to find out the marker of possitive HbsAg. The independent variable was blood transfussion history, the use of shrynge, piercing , permanent tattoo, accupunture, mouth cavity examination or dentist, family history of hepatitis,the tooth brush sharing or nail cutter.The resut showed that out of 97 female students subjected to blood test, 2 had a possitive HbsAg. Univariate analysis showed that factors associated with hepatitis B is the family history (OR=7.636; 95% Cl= 0.445-130.985 p=0,002). Multivariate analysis showed that family history of hepatitis B was significantly associated with the hepatitis B incidence (OR= 5. 704; 95% Cl= 0. 287-113. 276, p=0.004). Family history of hepatitis B is the risk factor for hepatitis B incidence in Pondok Pesantren Putri Ibnul Qoyyim Yogyakarta. Health education on the risk of geeting infected by Hepatitis B virus should be in the first priority.